2006
DOI: 10.1215/s0012-7094-06-13534-2
|View full text |Cite
|
Sign up to set email alerts
|

Birkhoff normal form for partial differential equations with tame modulus

Abstract: We prove an abstract Birkhoff normal form theorem for Hamiltonian Partial Differential Equations. The theorem applies to semilinear equations with nonlinearity satisfying a property that we call of Tame Modulus. Such a property is related to the classical tame inequality by Moser. In the nonresonant case we deduce that any small amplitude solution remains very close to a torus for very long times. We also develop a general scheme to apply the abstract theory to PDEs in one space dimensions and we use it to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
404
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(449 citation statements)
references
References 27 publications
8
404
0
Order By: Relevance
“…[Wan08]). Actually in the case studied in [Bou96,Bam03,BG06], the linear modes (i.e. the eigenfunctions of the linear part) are localized around the exponentials e ikx , i.e.…”
Section: Introduction Statement Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Wan08]). Actually in the case studied in [Bou96,Bam03,BG06], the linear modes (i.e. the eigenfunctions of the linear part) are localized around the exponentials e ikx , i.e.…”
Section: Introduction Statement Of the Resultsmentioning
confidence: 99%
“…The proof that there exists a set F k ⊂ W k whose measure equals 1 such that if m = (m j ) j∈N ∈ F k then the frequency vector (ω j ) j≥1 is non resonant is exactly the same as the proof of Theorem 5.7 in [Gré07]. So we do not repeat it here (see also [BG06]). …”
Section: Dynamical Consequencesmentioning
confidence: 95%
“…over an interval of length c N −N for any N ) for equation (1.1.2) on T 1 . This has been done by Bourgain [5], Bambusi [1], Bambusi-Grébert [3]. Such an almost global theorem has been proved in higher dimensions as well by Bambusi, Delort, Grébert and Szeftel [2] for equation (1.1.2) on the sphere S d (or more generally on a Zoll manifold).…”
Section: Statement Of the Main Theoremmentioning
confidence: 90%
“…The aim of this paper is to study long-time existence problems for semi-linear Klein-Gordon equations of type This problem has been studied in dimension 1 by Bourgain [5], Bambusi [1], Bambusi-Grébert [3]. They showed that one has then almost global existence: for any N , if the data are in H s+1 × H s Mathematics Subject Classification: 35L70.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively one could make use of inequalities obtained in more elementary ways by Bambusi [1] and Bambusi and Grébert [2].…”
Section: Proof Of Long-time Existencementioning
confidence: 99%